CHANGING ENVIRONMENT AND HUMAN BEHAVIOR: बदलता पर्यावरण और मानव.व्यवहार - Mehra, Archana (International Journal of Research -GRANTHAALAYAH, 2015)
There is a close relationship between human and environment. Often we blame a person for some bad act, but the truth is that the environment is equally guilty in it, so today human existence is in danger due to damage to the environment. Now awakening of environmental consciousness has become very essential because the environment surrounds human society, not just in physical form but also in social form. By observing a person’s behavior, his environment can be easily estimated. In this landscape, forest groves, river, mountain, fauna as well as climate and population all play an important role. Whenever there is an imbalance in them, human behavior also starts to become imbalanced. It has been proved scientifically. Therefore, there is a great need for ecological co-ordination in both environment and humans. This cannot be ignored at all. मानव और पर्यावरण के बीच घनिष्ठ सम्बन्ध है। प्रायः हम किसी बुरे कार्य के लिए व्यक्ति को दोष देते है किन्तु सच्चाई यह है कि उसमें पर्यावरण भी उतना ही दोषी होता है, अतः पर्यावरण की क्षति के कारण आज मानव का अस्तित्व संकट में पड़ गया है। अब पर्यावरण चेतना को जगाना अतिआवष्यक हो गया है क्योंकि पर्यावरण भौतिक रूप में नहीं सामाजिक रूप मंे भी मानव समाज को घेरे हुए है। किसी व्यक्ति के व्यवहार को देखकर उसके पर्यावरण का सहज अनुमान लगाया जा सकता है। इसमें प्राकृतिक दृष्य, वन उपवन, नदी, पर्वत, जीव जन्तु के साथ-साथ जलवायु और जनसंख्या इन सबकी महत्वपूर्ण भूमिका होती है। इनमें जब भी असंतुलन होता है, मानव व्यवहार भी असंतुलित होने लगता है। यह वैज्ञानिक सिद्ध कर चुके है। अतः पर्यावरण और मनुष्य दोनों में पारिस्थितिक समन्वय की अत्यधिक आवष्यकता है। इसे बिल्कुल नज़रअंदाज नहीं किया जा सकता है।